Copyright Exceptions for Teaching and Research Purposes: A Comparative Study Between Palestine and Malaysia - Mohammed Mahmoud Qtait; Muhammad Nizam Awang; Haliza A Shukor; Intan Nadia Ghulam Khan (UUM Press, 2024)
Indexed by Scopus/MyCite